A 6-hour light-dark cycle reduces photosynthesis and leaf greenness in spring wheat at stem elongation through nitrate accumulation - Clauw, Helena; Van de Put, Hans; Sghaier, Abderahman; Kerkaert, Trui; Vermeir, Pieter; Steppe, Kathy (Frontiers in Plant Science, 2025)
IntroductionThe closed environments of space farming and vertical farming systems allow for the implementation of innovative short light-dark cycles. These cycles have the potential to accelerate plant development and synchronize the short light period with off-peak electricity prices, thereby maximizing profitability. Previous work showed that growing spring wheat (Triticum aestivum L.) under a 6h-6h light-dark cycle resulted in accelerated heading. MethodsThe present study investigates pre-anthesis development under this photoperiod, with a focus on the stem elongation phase as critical period for yield determination. In addition, the effect of transitioning to a 14h-10h light-dark cycle, mimicking spring conditions in the field, at heading was examined. This was assessed across sequential growth chamber experiments in combination with variations in light intensity and CO2 concentration. Wheat phenology and leaf traits, including SPAD values, nitrogen and nitrate content and photosynthetic rates, were monitored. ResultsSPAD values, and thus leaf greenness, declined significantly in leaves developing around the start of stem elongation, leading to reduced photosynthetic rates. In these leaves, nitrate accumulation was detected. SPAD values increased following the shift to a 14h-10h light-dark cycle at heading, coinciding with higher photosynthetic rates. DiscussionThese findings underscore the importance of aligning photoperiod regimes with plant developmental stages to optimize wheat production in controlled environments.